(untitled) (Jurnal Ampere, 2023)
Currently, the use of this ice machine still uses a solenoid connected to a capillary and the results cannot be targeted. The use of an ice machine with the ESP8266 module is combined with the blynk application which is a combination with the Internet of Thinks (IoT) system which makes the performance of using the ice machine can be run remotely or with a smartphone. Reduced costs and less operator effort to expend for ice making. The ice machine was finally integrated with the ESP8266 Module, the blynk application and added with one solenoid connected to an expansion which functions as a substitute for the capillary selenoid if the need for ice is needed quickly in the process and will return to the capillary selenoid during normal production. The results showed that the ice machine with capillary selenoid was slower in the ice production process with 1 hour of production time of 5 kg of ice and required electricity consumption during production of 0.814 KWH, while the ice machine after using selenoid expansion the machine production process was faster than the capillary selenoid system by producing ice production for 1 hour with a yield of 8 kg of ice and requires electricity consumption during production of 0.855 KWH, with pressure for expansion of 18 bar.